2019
DOI: 10.1177/1591019919844946
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of stroke in children under 2 years with heart failure and ventricular assist device

Abstract: Introduction Strokes in children are characterised by a high mortality rate while, at the same time, the low number of cases makes it difficult to gain practical experience. As heart disease is the most common risk factor, and as more and more cardiological interventions are being carried out, an increase in the incidence of paediatric stroke is expected. In some cases a transplant is required. While waiting for a donor, the use of ventricular assist devices may be ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Although, several studies have shown that Open access endovascular clot retrieval and thrombolysis in adult stroke and in some children have excellent results. [20][21][22][23][24][25][26][27][28][29] In our study, no thrombolysis or mechanical thrombectomy was used and antithrombotic and anticoagulation use was only observed in 17.44% and 5.23% of patients who had an AIS. The low rate of thrombolysis and antithrombotic use may be related to delayed hospital visit and delayed diagnosis.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Although, several studies have shown that Open access endovascular clot retrieval and thrombolysis in adult stroke and in some children have excellent results. [20][21][22][23][24][25][26][27][28][29] In our study, no thrombolysis or mechanical thrombectomy was used and antithrombotic and anticoagulation use was only observed in 17.44% and 5.23% of patients who had an AIS. The low rate of thrombolysis and antithrombotic use may be related to delayed hospital visit and delayed diagnosis.…”
Section: Discussionmentioning
confidence: 55%
“…Onset-to-door time delay in our patients may be related to the aetiologies, as AIS was more likely to be caused by moyamoya in our study. Although, several studies have shown that endovascular clot retrieval and thrombolysis in adult stroke and in some children have excellent results 20–29. In our study, no thrombolysis or mechanical thrombectomy was used and antithrombotic and anticoagulation use was only observed in 17.44% and 5.23% of patients who had an AIS.…”
Section: Discussionmentioning
confidence: 56%